Taxonomic status of the genus Lunakia, including a redescription of the male and female genitalia of Lunakia alyssella (Klimesch, 1941) (Lepidoptera, Plutellidae) - Baraniak, Edward; Huemer, Peter (Zootaxa, 2024)
The genital morphology of the Lunakia alyssella (Klimesch, 1941) is redescribed. Additional details of both male and female genitalia are provided, supplemented with accompanying drawings. Anatomical evidence confirms that the genus Lunakia is distinct from the genus Eidophasia within the family Plutellidae. Males are characterized by long, curved appendages of the tegumen, and females by the antrum with a subgenital plate.